C-C and C-X coupling reactions of unactivated alkyl electrophiles using copper catalysis - Cheng, Li-Jie; Mankad, Neal P (Chemical Society reviews, 2020)
Transition metal-catalysed cross-coupling reactions are widely used for construction of carbon-carbon and carbon-heteroatom bonds. However, compared to aryl or alkenyl electrophiles, the cross-coupling of unactivated alkyl electrophiles containing β hydrogens remains a challenge. Over the past few years, the use of suitable ligands such as bulky phosphines or N-heterocyclic carbenes (NHCs) has enabled reactions of unactivated alkyl electrophiles not only limited to the traditional cross-coupling with Grignard reagents, but also including a diverse range of organic transformations via either S N 2 or radical pathways. This review provides a comprehensive overview of the recent development in copper-catalysed C-C, C-N, C-B, C-Si and C-F bond-forming reactions using unactivated alkyl electrophiles. Copper catalysts enable cross-coupling reactions of unactivated alkyl electrophiles to generate C-C and C-X bonds.